2009
DOI: 10.1089/end.2009.0080
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transabdominal Transvesical Vesicovaginal Fistula Repair

Abstract: Laparoscopic transvesical vesicovaginal fistula repair appears to be a safe and effective procedure that adheres to the principles of a transabdominal transvesical fistula repair while decreasing morbidity and improving cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…Subsequently, laparoscopic repair. 11 and robot-assisted repair. 12 Successful closure of some cases of small size VVF with prolonged catheterisation have been reported by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, laparoscopic repair. 11 and robot-assisted repair. 12 Successful closure of some cases of small size VVF with prolonged catheterisation have been reported by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the approach chosen should be that with which the surgeon is most comfortable (5,6) Laparoscopic VVF repair by different approaches has been described. Nezhat et al (7) were the first to report the laparoscopic retrovesical approach in 1994, which decreases the morbidity of the abdominal approach with similar success rates that range from 86% to 100% and minimal surgical trauma, allowing for more rapid convalescence (8,(10)(11)(12)(13)(14)(15)(16). Sotelo et al (8) reported an approach in which the bladder is first intentionally opened, accurately leading to the fistulous tract without requiring additional vaginal incisions or further dissection of the vesicovaginal space.…”
Section: Discussionmentioning
confidence: 99%
“…Sotelo et al (8) reported an approach in which the bladder is first intentionally opened, accurately leading to the fistulous tract without requiring additional vaginal incisions or further dissection of the vesicovaginal space. Thus, laparoscopy enables a limited cystostomy that improves upon the historically morbid O'Connor procedure, in which the bladder is bi--valved to the level of the fistula (12). Using the technological advantages of robotic technology (EndoWrist TM instruments with increased degrees of freedom leading to improved dexterity and absence of fatigue, three-dimensional [3-D] vision with improved depth perception, motion scaling, tremor filtration, higher magnification, and the surgeon's ergonomic position in a longstanding and time-consuming operation), it is possible to perform laparoscopic repair of VVF with robotic assistance, respecting the basic surgical principles of fistula reconstruction (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recientemente publicamos nuestra experiencia en la reparación laparoscópica de FVV en 8 casos demostrando ser un abordaje factible y seguro que puede reproducir los pasos de la cirugía convencional 5 . No obstante, al ser una patología infrecuente, las series publicadas son de pocos casos (Tabla 1) [7][8][9][12][13][14][15] . La serie con mayor Recientemente se ha incorporado a nuestros recursos quirúrgicos la cirugía robótica (da Vinci®) que es posible que pueda aportar ventajas comparativas o superiores a la vía laparoscópica 16,17 .…”
Section: Discussionunclassified